ANALISIS FUNGSI PRODUKSI DAN EFISIENSI ALOKATIF USAHATANI UBI JALAR DI KECAMATAN HULU PALIK KABUPATEN BENGKULU UTARA - Simanjuntak, Bripen; Sukiyono, Ketut; Sriyoto, Sriyoto (Jurnal AGRISEP, 2019)
The aims of the research are to 1) determine factors that affect the production of sweet potato, 2) to determine the level of allocative efficiency of sweet potato production inputs. The location of this study was determined purposively, in the Subdistrictof Hulu Palik, North Bengkulu Regency with consideration that in Hulu Palik Subdistrict is the biggest producer of sweet potato in North Bengkulu Regency. Census of 92 farmers carried out to gather data on sweet potato farming. Data analysis used multiple linear regression method using Cobb-Douglas production function and allocative efficiency analysis. The results showed that the factors of production of land area of sweet potato seeds and phonska fertilizer had a significant and positive effect on sweet potato production. Results The analysis of allocative efficiency shows the Marginal Product Value of the production factor of land area, sweet potato seed and phonska fertilizer greater than one. This means that the use of phonska production factors for land area, seeds, and fertilizer is not yet efficient